(untitled) (Revista Contexto & Saúde, 2023)
Several people suffer from diseases and injuries and many of them die because of late diagnostic and/or inefficient treatment. Many of these diseases affect humans and animals, and animals can be vectors for humans. In this perspective, it is necessary works that integrate humans, animals, and ecosystems, thus, to arise the One Health. Along with it, nanotechnology is a great alternative to improve health care, due to its revolutionary and complex properties. Although, how can nanomaterials be capable of work with or against cells, tissues, drugs, and medical devices? There are already many products in the market, but there are a lot of challenges to face and a whole new world to discover. In this article are given the application of nanostructures in diagnostic, therapy, medical devices, tissue and implant engineering, human health and animal, and a future perspective.